2021
DOI: 10.4149/neo_2021_201210n1341
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the expression and response of PD-1, LAG-3, and TIM-3 after neoadjuvant radiotherapy in rectal cancer

Abstract: Many studies have verified the safety of combined radiotherapy and immune checkpoint blockades iation dose or sequencing of combination. We aimed to evaluate the expression and response of PD-1, TIM-3, LAG-3 after neoadjuvant radiotherapy (NRT) and explore the possibility and optimal schedule of combining immunotherapy with radiotherapy in treating rectal cancer. Immunohistochemistry was performed to detect the expression of PD-1, TIM-3, LAG-3, CD8, and CD3. These molecules' expression was detected on the spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Peng et al found that the expression of LAG3 after neoadjuvant radiotherapy (NRT) significantly increased in rectal cancer, especially for short-term NRT, and that this high expression may induce a better treatment effect. Thus, it is reasonable to consider that the combination of NRT with immunotherapy may be an alternative for patients with advanced rectal cancer (76).…”
Section: Clinical Application Of Lag3/fgl Treatment and Curative Effectmentioning
confidence: 99%
“…Peng et al found that the expression of LAG3 after neoadjuvant radiotherapy (NRT) significantly increased in rectal cancer, especially for short-term NRT, and that this high expression may induce a better treatment effect. Thus, it is reasonable to consider that the combination of NRT with immunotherapy may be an alternative for patients with advanced rectal cancer (76).…”
Section: Clinical Application Of Lag3/fgl Treatment and Curative Effectmentioning
confidence: 99%
“…Two studies each explored the survival outcome of patients with BLCA [ 36 , 63 ], COAD [ 39 , 49 ], LIHC [ 34 , 42 ], THCA [ 44 , 53 ], STAD [ 45 , 47 ], and SKCM [ 38 , 40 ]. Only one study each reported the survival outcome of non-small cell lung cancer (NSCLC) [ 35 ], CESC [ 66 ], KIRC [ 33 ], SARC [ 41 ], READ [ 48 ], COADREAD [ 58 ], PAAD [ 52 ], and UCEC [ 65 ]. Thirty-two of the included studies reported the correlation between LAG3 expression and OS [ 24 35 , 37 , 38 , 40 , 42 , 44 47 , 50 , 51 , 54 59 , 62 64 , 66 ], fourteen reported the correlation LAG3 expression and DFS [ 24 26 , 33 , 34 , 39 , 42 , 43 , 45 , 46 , 48 , 49 , 52 , 60 ], ten reported the correlation between LAG3 expression and PFS [ 37 , 38 , 41 , 47 , 50 , 61 64 , 66 ], and eight reported the correlation between LAG3 expression and RFS [ 27 , 31 , 35 , 36 , 53 ...…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies involving 2,026 patients investigated the correlation between the expression of LAG3 and DFS [ 24 26 , 33 , 34 , 39 , 42 , 43 , 45 , 46 , 48 , 49 , 52 , 60 ]. The pooled analysis showed that there was no significant correlation between LAG3 expression and DFS (HR = 1.41, 95% CI 0.96–2.07, P = 0.078), as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The role of LAG-3 and TIM-3 has not been extensively studied in rectal cancer (Tables 2 and 3). Peng et al investigated the expression of LAG-3 and TIM-3 in 76 rectal cancer patients treated with preoperative RT [106]. LAG-3-expressing immune cells increased in cancer tissues after RT, while TIM-3 decreased.…”
Section: Other Immune-related Pathwaysmentioning
confidence: 99%